Golden Buttons : Christianity and Tradition Religion among the Tumbuka - Msiska, Stephen Kauta, 1914?- (Luviri reprints, 2018)
Stephen Kauta Msiska was ordained to the ministry in 1945 and served the Livingstonia Synod in a number of lakeshore parishes before being appointed first a tutor and later Principal of the united CCAP Theological College at Nkhoma where he taught from 1962 to 1974. His firm stand for what he understood to be the principles of the Christian Gospel led to a clash with the one-party regime and he was forced to flee to his home village and to live there in relative obscurity. This book makes accessible some of the fruits not only of his years of active pastoral ministry and theological teaching but also of his time of lonely suffering and sorrow. Distinctive in the writing of this pioneering theologian is a profound, though not uncritical, sympathy with the traditional religion of his people combined with a passionate concern for authentic Christian discipleship. Careful readers of this original and thoughtful book will find the "golden buttons" which Stephen Kauta is determined should not be lost.